Olfactory rehabilitation and olfactory bulb volume changes in patients after total laryngectomy: a prospective randomized study - Gürbüz,Defne (2022)
Abstract Introduction: After total laryngectomy, decreased olfactory function and olfactory bulb volume shrinkage have been reported to occur due to olfactory deprivation caused by nasal airflow interruption. There is evidence that the olfactory system can be modulated by repeated exposure to odors in a procedure called olfactory training. However, it is not known whether any recovery of the lost olfactory bulb volume is possible by eliminating olfactory deprivation via olfactory rehabilitation long after laryngectomy. Objective: This study examined the recovery of olfactory function and the change in olfactory bulb volume via long-term olfactory rehabilitation after total laryngectomy. Methods: Possible causes of olfactory dysfunction in the study participants were evaluated by collecting detailed anamnesis. As olfactory tests, orthonasal butanol threshold and odor discrimination tests were performed. Three-dimensional olfactory bulb volumes were calculated using manual segmentation on T2-weighted coronal magnetic resonance images. In olfactory rehabilitation, four different odors were applied to all patients orthonasally, using a larynx bypass technique for 30 min per day for 6 months. Olfactory tests were performed before the rehabilitation and after 6 months of rehabilitation, and olfactory bulb volume measurements were performed using magnetic resonance images. Results: Eleven patients diagnosed with advanced laryngeal cancer who underwent total laryngectomy and postoperative radiotherapy with a follow-up of 5–10 years were included in the study. All patients were male, and the mean age was 58.18 ±4.17 years. In total laryngectomized patients, the olfactory bulb volumes measured on magnetic resonance images were 42.25 ± 12.8 mm3 before and 55.5 ± 11.22 mm3 after rehabilitation, and this increase was highly significant. Olfactory test scores were 2.3 ± 1.27 before and 4.39 ± 0.86 after rehabilitation, and this increase was also highly significant. Conclusion: As a result of the olfactory rehabilitation applied by providing orthonasal air flow, the olfactory function lost after total laryngectomy was improved considerably, and the olfactory bulb volume was significantly increased. The increase in olfactory bulb volume in total laryngectomy patients via olfactory rehabilitation to eliminate olfactory deprivation due to nasal airflow interruption was demonstrated for the first time in this prospective longitudinal study.